The Level of Awareness of Students of Faculty of Physical Education at Yarmouk University of the Importance of Public Health - Alkhaldi, Tharwat Sayel; Alsalem, Hani (Dirasat: Educational Sciences, 2020)
This study aims to identify the level of awareness of the students of the Faculty of Physical Education at Yarmouk University of the importance of public health. The researchers used a descriptive approach, and their sample consisted of (300) male and female students who were chosen randomly. The participants answered questions on a scale that consisted of (40) statements distributed on five domains (nutrition, physical activity, stature, personal health, and disease prevention). The results of the study indicated that the level of awareness of the importance of public health was moderate, as it was found that there were statistically significant differences at the significance level (0.05 ≥α) due to the effect of gender in all the domains except for the domains of nutrition and exercise, and the differences were in favor of females. There were no statistically significant differences (α ≤ 0.05) due to the effect of academic level and place of residence. The study recommends the need to pay attention to the issue of public health and nutritional culture and work to include it within the university curricula, and to include some courses related to health and food within the compulsory university requirements.